Grievances, economic wealth, and civil conflict. (January 2014) - Koubi, Vally; Böhmelt, Tobias
One of the most robust findings in the literature on civil conflicts is that high income levels are associated with a lower risk of conflict onset. This article addresses the wealth-conflict link and discusses it in relation to the dominating `greed vs. grievance' dichotomy. It is further argued that the effect on conflict of grievances, in the form of horizontal inequalities, is conditioned on national wealth. More specifically, there may be a higher risk of civil war in those countries that have much wealth, but where a large share of the population is potentially excluded from accessing it. The empirical analyses testing this argument employ time-series cross-section data for 1951–2004 and find support for the theory. The authors also show that taking this conditional relationship into account improves our ability to predict the onset of civil conflict.